2023
DOI: 10.15252/embj.2023113578
|View full text |Cite
|
Sign up to set email alerts
|

The Ebola virus VP40 matrix layer undergoes endosomal disassembly essential for membrane fusion

Abstract: Ebola viruses (EBOVs) assemble into filamentous virions, whose shape and stability are determined by the matrix viral protein 40 (VP40). Virus entry into host cells occurs via membrane fusion in late endosomes; however, the mechanism of how the remarkably long virions undergo uncoating, including virion disassembly and nucleocapsid release into the cytosol, remains unknown. Here, we investigate the structural architecture of EBOVs entering host cells and discover that the VP40 matrix disassembles prior to memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 111 publications
1
8
0
Order By: Relevance
“…Unlike influenza viruses, arenaviruses do not have proton channels in their lipid envelope that actively acidify the virion upon endocytosis. However, it has recently been shown for LASV that protons passively cross the viral membrane, which leads to acidification of the virus interior prior to membrane fusion. , Similar observations have been reported for Ebola virus, where acidification of virions leads to viral matrix reorganization . Besides the pH-dependent NP–Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unlike influenza viruses, arenaviruses do not have proton channels in their lipid envelope that actively acidify the virion upon endocytosis. However, it has recently been shown for LASV that protons passively cross the viral membrane, which leads to acidification of the virus interior prior to membrane fusion. , Similar observations have been reported for Ebola virus, where acidification of virions leads to viral matrix reorganization . Besides the pH-dependent NP–Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5.…”
Section: Discussionsupporting
confidence: 93%
“…32,33 Similar observations have been reported for Ebola virus, where acidification of virions leads to viral matrix reorganization. 62 Besides the pH-dependent NP−Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5. We hypothesize that stronger Z−Z interaction at low pH, as indicated by oligomerization, further reduces availability of Z for the low-affinity Z−NP interaction.…”
Section: ■ Discussionmentioning
confidence: 78%
“…This phenomenon may be even more widespread among viruses. Winter et al have recently reported that passive acidification of the Ebola virus interior induces profound structural changes in the virion including the dissociation of the VP40 matrix layer from the viral membrane [66]. Further studies are needed to define the molecular mechanism for arenavirus PVMP and its role in its role in the early steps of arenavirus infection.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The presence of the support significantly increases the tension-independent contribution to stalk energy, F 0 , since the stalk formation involves local membrane detachment from the support. 47 However, the tension-dependent term, F T , is not significantly affected; while a negligible amount of membrane is withdrawn from the supported membrane, almost double the amount is drawn from the free membrane, resulting in a similar ΔA. To estimate the correction, we assume that the stalk shape at the GUV side is unaffected by the bead support.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, our experimental setting allows us to set the tension in the GUV membrane but not in the bead, which acts as a tight membrane support. The presence of the support significantly increases the tension-independent contribution to stalk energy, F 0 , since the stalk formation involves local membrane detachment from the support . However, the tension-dependent term, F T , is not significantly affected; while a negligible amount of membrane is withdrawn from the supported membrane, almost double the amount is drawn from the free membrane, resulting in a similar Δ A .…”
Section: Results and Discussionmentioning
confidence: 99%